1997
DOI: 10.1046/j.1471-4159.1997.69041459.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Catecholamines by Catechol‐O‐Methyltransferase in Cells Expressing Recombinant Catecholamine Transporters

Abstract: Abstract:To determine if catechol-O-methyltransferase (COMT) metabolizes catecholamines within cell lines used for heterologous expression of plasmalemmal transporters and alters the measured characteristics of 3H-substrate transport, the uptake of monoamine transporter substrates was assessed in three cell lines (C6 glioma, L-M fibroblast, and HEK293 cells) that had been transfected with the recombinant human transporters. Uptake and cellular retention of 3H-catecholamines was increased by up to fourfold by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 17 publications
5
40
1
Order By: Relevance
“…Average levels of dopamine and serotonin in FBS present in cell cultures over 24 h were probably even lower than initial levels; recent experiments have shown that catechol-O-methyltransferase actively degrades monoamines in several cell cultures expressing recombinant DAT cDNA (Eshleman et al, 1997). In any case, as shown in Fig.…”
Section: Effects Of Cocainementioning
confidence: 78%
“…Average levels of dopamine and serotonin in FBS present in cell cultures over 24 h were probably even lower than initial levels; recent experiments have shown that catechol-O-methyltransferase actively degrades monoamines in several cell cultures expressing recombinant DAT cDNA (Eshleman et al, 1997). In any case, as shown in Fig.…”
Section: Effects Of Cocainementioning
confidence: 78%
“…The resulting pellet was then resuspended in 3 ml of buffer and homogenized with a Polytron homogenizer at setting 7 for 5 to 10 s. The assays contained approximately 75 to 150 g of membrane protein for DHTB binding (less than 15% of the radioactivity added was bound), or 25 to 50 g of membrane protein for RTI-55 binding (less than 25% of radioactivity added was bound), drug, and jpet.aspetjournals.org methyl transferase (COMT) inhibitor] were included in the buffer so that results could be compared with studies done using tissue from animals, which require the addition of MAO and COMT inhibitors. In previous studies, Vindis et al (2000) found no evidence for MAO activity in HEK-293 cells; however, other studies suggest the presence of COMT activity in HEK-293 cells (Eshleman et al, 1997). Pifl et al (1995) using African green monkey kidney (COS-7) cells, in the absence of MAO or COMT inhibitors, reported that 70 to 80% of the tritium released from hDAT cells and 80 to 90% of the tritium released from hDAT/rVMAT2 cells was [ 3 H]DA, suggesting that DA metabolites comprise only a small part of the recovered tritium.…”
Section: Materials [mentioning
confidence: 86%
“…Furthermore, chronic antidepressant treatment has been shown to increase the expression and release of glial cell-derived neurotrophic factor (GDNF) (33)(34)(35). Curiously, the molecular entities most commonly associated with antidepressants, serotonin and norepinephrine transporters, are not endogenously expressed in C6 cells (36), which still respond to antidepressants by mediating lipid raft translocation of G␣ s .…”
Section: Discussionmentioning
confidence: 99%